Randomized trial of steroid free immunosuppression with basiliximab induction in adult live donor liver transplantation (LDLT). Issue 5 (May 2021) - Kathirvel, Manikandan; Mallick, Shweta; Sethi, Pulkit; Thillai, Manoj; Durairaj, Madhu S.; Nair, Krishnanunni; Sunny, Aleena; Mathew, Johns S.; Varghese, Christi T.; Chandran, Biju; Pillai Thankamony Amma, Binoj S.; Menon, Ramachandran N.; et al.
Abstract: Background: Corticosteroids are an integral part of immunosuppression following solid organ transplantation, despite their metabolic complications. We conducted a randomized trial to evaluate the efficacy of steroid-free immunosuppression following live donor liver transplantation (LDLT). Methods: We randomized 104 patients stratified based on pre-transplant diabetic status to either a steroid-free arm (SF-arm) (Basiliximab + Tacrolimus and Azathioprine, n = 52) or Steroid arm (S-Arm) (Steroid + Tacrolimus + Azathioprine, n = 52). The primary endpoint was the occurrence of metabolic complications (new-onset diabetes after transplant (NODAT), new-onset systemic hypertension after transplant (NOSHT), post-transplant dyslipidemia) within 6 months after transplant. Secondary endpoints included biopsy-proven acute rejection (BPAR) within six months, patient and graft survival at 6 months. Results: The incidence NODAT was significantly higher in S-arm at 3 months (64.5%vs. 28.1%, p-0.004) and 6 months (51.6% vs. 15.6%, p-0.006). Likewise, the incidence of NOSHT (27.8% vs. 4.8%, p-0.01) and hypertriglyceridemia (26.7% vs. 8%, p-0.03) at six months was significantly higher in S-arm. However, there were no differences in BPAR (19.2% vs. 21.2%, p-0.81), time to first rejection (58 vs. 53 days, p-0.78), patient and graft survival (610 vs. 554 days, p- 0.22). Conclusion: Following LDLT, basiliximab induction with tacrolimus and azathioprine maintenance resulted in significantly lower metabolic complications compared to the triple-drug regimen of steroid, tacrolimus, and azathioprine.